Transcriptomics Analysis of Penicillium expansum ΔWSC1 Infection and Defense Mechanism against It in Pear Fruits - ZHAO Lina, HU Yize, SHU Yuling, Solairaj DHANASEKARAN, ZHANG Xiaoyun, YANG Qiya, ZHANG Hongyin (Shipin Kexue, 2025)
The WSC proteins produced by Penicillium expansum play a crucial role in causing blue mold on pears. To analyze the role of the WSC1 gene in the pathogenic process of this fungal pathogen, we conducted transcriptomic analysis of a WSC1 knockout (ΔWSC1) strain. The knockout of WSC1 significantly altered the gene expression profile in P. expansum, particularly for genes involved in cell wall integrity, signaling, stress response, and toxin production. The differential expression of these genes might make the ΔWSC1 strain more vulnerable to environmental stress, while reducing the toxin production capacity, ultimately leading to a decrease in the pathogenicity. The transcriptomic analysis revealed that the expression of genes related to stress response signals, defense mechanisms and oxidative stress management changed when pear fruits were infected with the ΔWSC1 strain. These changes may trigger a cascade of responses in pear fruits. In addition, compared with those infected with the wild-type strain, pear fruits infected with the ΔWSC1 strain exhibited up-regulated expression of genes related to defense and oxidative stress. This study clarifies how the WSC1 gene influences P. expansum’s ability to infect pear fruits and how pear fruits respond to the infection.